2021
DOI: 10.1002/anie.202103382
|View full text |Cite
|
Sign up to set email alerts
|

Chirogenesis and Amplification of Molecular Chirality Using Optical Vortices

Abstract: The study of chirogenesis of organic molecules is important to elucidate the origin of the homochirality of biomolecules on Earth. Here, we have accomplished chiral symmetry breaking from a racemate using optical vortices with orbital angular momentum and a helical wavefront. We propose a new methodology of asymmetric transformation by the combination of enantioselective crystal nucleation by irradiation with optical vortices and crystallization-induced dynamic optical resolution of conglomerate crystals. Chir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…[28] In spontaneous dynamic crystallization, the chirality of the crystal was determined by the initially generated crystal nucleus and the nucleus was amplified under deracemization conditions based on dynamic crystal-lization. [29] One-handed enantiomorphic isoindolinone 1 was easily obtained by crystallization from solution by evaporation of the solvent in the presence of 1,8-diazabicyclo-[5.4.0]undec-7-ene (DBU) as a base. The racemization involving ring opening and closing reactions was accelerated by DBU, and almost optically pure enantiomorphic crystals were easily obtained after chiral symmetry breaking.…”
Section: Resultsmentioning
confidence: 99%
“…[28] In spontaneous dynamic crystallization, the chirality of the crystal was determined by the initially generated crystal nucleus and the nucleus was amplified under deracemization conditions based on dynamic crystal-lization. [29] One-handed enantiomorphic isoindolinone 1 was easily obtained by crystallization from solution by evaporation of the solvent in the presence of 1,8-diazabicyclo-[5.4.0]undec-7-ene (DBU) as a base. The racemization involving ring opening and closing reactions was accelerated by DBU, and almost optically pure enantiomorphic crystals were easily obtained after chiral symmetry breaking.…”
Section: Resultsmentioning
confidence: 99%
“…[1] Generally, chirality appears at different hierarchical levels ranging from molecular to supramolecular levels, and chirality can be induced with the assembly of chiral substances or the combination of chiral and achiral substances with various structures, including helix, spiral, gyroid, toroid, and Moebius strips. [2,3] Recently, the origin Although a few works have reported the construction of chiroptical switches using azo polymers, including chiral gel, enantiopure tartaric acid, linearly polarized light, chiral solvents, and CPL. [18][19][20] However, a great challenge still remains.…”
Section: Introductionmentioning
confidence: 99%
“…Since Pasteur discovered molecular asymmetry, 1 the origin of biological chirality in nature has been an attractive mystery. 2 , 3 Among the theories, 4 − 9 isotopic chirality is a possibility 10 because many apparently achiral organic compounds become chiral when taking isotopic substitutions into consideration. 11 − 14 A higher deuterium-labeling ratio of meteoritic compounds than found in the same terrestrial compounds has been reported; 15 therefore, extra-terrestrial organic compounds may have isotopic chirality.…”
Section: Introductionmentioning
confidence: 99%
“…Since Pasteur discovered molecular asymmetry, the origin of biological chirality in nature has been an attractive mystery. , Among the theories, − isotopic chirality is a possibility because many apparently achiral organic compounds become chiral when taking isotopic substitutions into consideration. − A higher deuterium-labeling ratio of meteoritic compounds than found in the same terrestrial compounds has been reported; therefore, extra-terrestrial organic compounds may have isotopic chirality. Although chiral recognition technologies have been developed , and isotopically labeled compounds are often used to elucidate reaction mechanisms in the field of stereochemistry and biochemistry, chiral induction effects in asymmetric reactions are difficult to observe.…”
Section: Introductionmentioning
confidence: 99%